III-nitride semiconductor lasers grown on Si. (May 2021) - Feng, Meixin; Liu, Jianxun; Sun, Qian; Yang, Hui
Abstract: III-nitride semiconductor laser directly grown on Si is a potential on-chip light source for Si photonics. Moreover, it may greatly lower the manufacture cost of laser diodes and further expand their applications. Therefore, III-nitride lasers grown on Si have been pursued for about two decades. Different from GaN homoepitaxy on free-standing GaN substrates, III-nitride semiconductors grown on Si substrates are usually rich with strain and threading dislocations due to the large mismatch in both lattice constant and coefficient of thermal expansion between GaN and Si substrates, which hindered the realization of electrically injected lasing. The key challenges in the direct growth of high-quality III-nitride semiconductor laser materials on Si substrates, as well as their corresponding solutions, are discussed in detail. Afterwards, a comprehensive review is presented on the recent progress of III-nitride semiconductor lasers grown on Si, including Fabry-Pérot cavity lasers, microdisk lasers, and the lasers with nanostructures, as well as the monolithic integration of lasers on Si. Finally, the further development of III-nitride semiconductor lasers grown on Si is also discussed, including the material quality improvement and novel device structures for enhancing optical confinement and reducing electrical resistance, with a great prospect for better performance and reliability.